Região metropolitana do Cariri – R.M.C.: uma análise a partir da política de desenvolvimento territorial - Pais, Henrique Luiz Rodrigues (2014)
This dissertation aims to conduct an analysis of the Metropolitan Region of Cariri (MRC) from the territorial development policy. The MRC is the second MR established in the state of Ceará, it was legalized in 2009 and currently covers nine municipalities. The chapters discuss about the perceptions of the various actors of the territory in which they relate to the current state of the MRC, its cooperative and competitive advantages or disadvantages, as well as dimensions that are giving the growth or territorial development and the improvement of human capital, social capital and sustainable use of natural capital. The research also presents a general overview of the MRC in its more than four years of existence by encouraging reflection on the possibility of a regional development process from the perspective of sustainability. The methodological approach is the qualitative method in order to achieve the proposed objectives. It is noteworthy that the nature of this study is exploratory and descriptive in order to make the discussed problem more explicit. Interviews related to the literature review and document analysis were the outlining chosen for the research.